Putusan Mahkamah Konstitusi Nomor 20/PHPU.BUP-XXIII/2025 tentang Sengketa Hasil Pilkada Kabupaten Pesawaran: Perspektif Siyasah Qadha’iyyah - Ika Mila Sari (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The purpose of this study is to reveal Constitutional Court Decision No. 20/PHPU.BUP-XXIII/2025 regarding the dispute over the results of the 2024 regional head elections in Pesawaran Regency from the perspective of Siyasah Qadha'iyyah. Using a normative qualitative method with a literature review approach, this study examines the judicial authority of the Constitutional Court and the application of Islamic legal principles in resolving election disputes. The findings indicate that the decision has embodied the principles of al-'adl (justice) and al-amanah (responsibility) by disqualifying candidates who violated administrative requirements and ordering a re-vote. However, the emergence of further legal challenges and prolonged leadership vacancies indicate ongoing challenges in achieving substantive justice and al-maslahah (public interest). This study concludes that the ruling, although procedurally adequate, requires improvement in terms of evidentiary standards, transparency mechanisms, and procedural efficiency to better align with the values of Siyasah Qadha'iyyah, which emphasizes a balance between justice, public interest, and social cohesion.